Object categorisation using Malay Shape-based numeral classifiers. - Khazriyati Salehuddin,; Winskel, Heather (Penerbit UKM, 2011)
Categorisation is fundamental in human cognition and language development. Crosslinguistic studies on categorisation propose numeral classifiers as a linguistic manifestation of human categorisation and conceptualisation. Thus, studies on numeral classifier acquisition enable researchers to examine how children learn to categorise objects in their environment using a constrained framework, and how this ability becomes more refined as children grow older. This study investigated the strategies children utilise in categorising objects into eight Malay shape-based numeral classifier categories using a paired discrimination task. One-hundred-and-forty-eight children ranging in age from 6 to 9 years and a comparison group of adults participated in this study. Results revealed that children categorised objects more readily when there was a strong (two-perceptual feature distinction) than weak (one-perceptual feature distinction) contrast, and when exemplars were typical rather than atypical. There appears to be a gradual transition from a perceptually biased to a broader, more rule-based system.